Trichomonas vaginalis Induces Production of Proinflammatory Cytokines in Mouse Macrophages Through Activation of MAPK and NF-κB Pathways Partially Mediated by TLR2 - Li, Ling; Li, Xin; Gong, Pengtao; Zhang, Xichen; Yang, Zhengtao; Yang, Ju; Li, Jianhua (Frontiers in Microbiology, 2018)
Trichomoniasis, caused by Trichomonas vaginalis infection, is the most prevalent sexually transmitted disease in female and male globally. However, the mechanisms by innate immunity against T. vaginalis infection have not been fully elucidated. Toll-like receptor2 (TLR2) has been shown to be involved in pathogen recognition, innate immunity activation and inflammatory response to the pathogens. Nonetheless, the function of TLR2 against T. vaginalis remains unclear. In the present study, we investigated the role of TLR2 in mouse macrophages against T. vaginalis. RT-qPCR analysis revealed that T. vaginalis stimulation increased the gene expression of TLR2 in wild-type (WT) mouse macrophages. T. vaginalis also induced the secretion of IL-6, TNF-α and IFN-γ in WT mouse macrophages, and the expression of these cytokines significantly decreased in TLR2-/- mouse macrophages and in WT mouse macrophages pretreated with MAPK inhibitors SB203580 (p38) and PD98059 (ERK). Western blot analysis demonstrated that T. vaginalis stimulation induced the activation of p38, ERK, and p65 NF-κB signal pathways in WT mouse macrophages, and the phosphorylation of p38, ERK and p65 NF-κB significantly decreased in TLR2-/- mouse macrophages. Taken together, our data suggested that T. vaginalis may regulates proinflammatory cytokines production by activation of p38, ERK and NF-κB p65 signal pathways via TLR2 in mouse macrophages. TLR2 might be involved in the defense and elimination of T. vaginalis infection.